2018
DOI: 10.1158/2159-8290.cd-17-0909
|View full text |Cite
|
Sign up to set email alerts
|

MACROD2 Haploinsufficiency Impairs Catalytic Activity of PARP1 and Promotes Chromosome Instability and Growth of Intestinal Tumors

Abstract: ADP-ribosylation is an important posttranslational protein modification that regulates diverse biological processes, controlled by dedicated transferases and hydrolases. Here, we show that frequent deletions (∼30%) of the mono-ADP-ribosylhydrolase locus in human colorectal cancer cause impaired PARP1 transferase activity in a gene dosage-dependent manner. haploinsufficiency alters DNA repair and sensitivity to DNA damage and results in chromosome instability. Heterozygous and homozygous depletion of enhances i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 50 publications
5
53
0
Order By: Relevance
“…Aberrant MacroD1 expression and gene fusions contribute to tumour pathology; e.g., in leukaemia, breast, gastric, liver, lung, and colorectal cancer (Imagama et al 2007;Shao et al 2015;Sakthianandeswaren et al 2018). Several lines of evidence indicate that MacroD1 is involved in several important signaling pathways: In breast cancer-derived MCF-7 cells, MacroD1 expression is induced by estrogenic hormones in an estrogen receptor alpha (ERα)-dependent manner and subsequently acts as a cofactor for ERα and the androgen receptor (Han et al 2007;Yang et al 2009).…”
Section: Macrod1 and Macrod2mentioning
confidence: 99%
“…Aberrant MacroD1 expression and gene fusions contribute to tumour pathology; e.g., in leukaemia, breast, gastric, liver, lung, and colorectal cancer (Imagama et al 2007;Shao et al 2015;Sakthianandeswaren et al 2018). Several lines of evidence indicate that MacroD1 is involved in several important signaling pathways: In breast cancer-derived MCF-7 cells, MacroD1 expression is induced by estrogenic hormones in an estrogen receptor alpha (ERα)-dependent manner and subsequently acts as a cofactor for ERα and the androgen receptor (Han et al 2007;Yang et al 2009).…”
Section: Macrod1 and Macrod2mentioning
confidence: 99%
“…The authors argue that, as a cancer specific fragile site, the MACROD2 gene can be lost, but this fragility also allows for amplification in the specific case of ER-positive breast cancers treated with tamoxifen to incur resistance. A more recent study showed that, in approximately one-third of colorectal carcinomas investigated, heterozygous or homozygous losses were mapped within the MACROD2 gene in which the majority are intragenic microdeletions mapping to a region in exons 4 to 5 [111]. To test whether MACROD2 deficiency can promote tumourigenesis, MACROD2 knockout was introduced into an adenomatous polyposis coli protein (Apc) mouse model.…”
Section: Macrod2 In Cancermentioning
confidence: 99%
“…To test whether MACROD2 deficiency can promote tumourigenesis, MACROD2 knockout was introduced into an adenomatous polyposis coli protein (Apc) mouse model. Mutations in the APC tumour suppressor are a major driver of sporadic colorectal cancers, where it could be shown that even haploinsufficiency of MACROD2 leads to more and larger adenoma formation [111]. Furthermore, human cells transplanted into nude mice displayed increased tumour growth when lacking MACROD2, but a reduced tumour growth when MACROD2 was overexpressed [111].…”
Section: Macrod2 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In the TGA subgroup, four SNPs with genome-wide significance mapped to MACROD2 which has been linked to adipogenesis and hypertension. 26,33 Microdeletions in this gene have been implicated as a cause of chromosomal instability in cancers 34 and de novo deletion of exon 5 causes Kabuki syndrome. 35 Chromosomal imbalance is also frequently seen in CHD patients with different morphologies [36][37][38][39] including TGA 40 but so far the MACROD2 locus was not associated with CHD.…”
Section: Tga and Macrod2mentioning
confidence: 99%